A new procedure, free from human assessment that automatically grades some facial skin structural signs. Comparison with assessments by experts, using referential atlases of skin ageing. (27th February 2019) - Jiang, Ruowei; Kezele, Irina; Levinshtein, Alex; Flament, Frederic; Zhang, Jingyi; Elmoznino, Eric; Ma, Junwei; Ma, He; Coquide, Jerome; Arcin, Vincent; Omoyuri, Esohe; Aarabi, Parham
Abstract: Objective: To develop an automatic system that grades the severity of facial signs through 'selfies' pictures taken by women of different ages and ethnics. Methods: 1140 women from three ethnics (African‐American, Asian, Caucasian), of different ages (18–80 years old), took 'selfies' by high resolution smartphones cameras under different conditions of lighting or facial expressions. A dedicated software, was developed, based on a Convolutional Neural Network (CNN) that integrates training data from referential Skin Aging Atlases. The latter allows to an immediate quantification of the severity of nine facial signs according to the ethnicity declared by the subject. These automatic grading were confronted to those assessed by 12 trained experts and dermatologists either on 'selfies' pictures or in live conditions on a smaller cohort of women. Results: The system appears weakly influenced by lighting conditions or facial expressions (coefficients of variations ranging 10–13% for most signs) and leads to global agreements with experts' assessments, even showing a better reproducibility on some facial signs. Conclusion: This automatic scoring system, still in development, seems offering a new quantitative approach in the quantified description of facial signs, independent from human vision, in many applications, being individual, cosmetic oriented or dermatological with regard to the follow‐up of medical anti‐ageing corrective strategies. Abstract : Examples of 4 'selfies' taken by an Asian woman under four different lighting conditions..